Kajian Perikanan Tangkap Mene maculata di Teluk Buyat - Fransisco P.T. Pangalila; Johny Budiman; Aglius T.R. Telleng; Emil Reppie (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
Moonfish (Mene maculata) known locally as bete tamako or peda cina, is one of the  economically important fish resources resulting from Buyat Bay. Although it has relatively small size (estimated length 25-30 cm), but the fish has a good taste. The presence of moonfish is usually a sign of sailfish fishing season in the Buyat Bay. Common fishing gear used to catch moonfish is hand line , noru.  However, scientific information about the status of moonfish fishery was not yet understood. Therefore, this study aims to determine the status of moonfish fishery and map out the fishing location.  This research was conducted in the Buyat Bay, Ratatotok District, Southeast Minahasa Regency (March-September 2013); using a survey method with a descriptive approach. Catch data were analyzed by a surplus production model.  These results informed that the maximum sustainable yields (MSYs)  was 1707 fish/trip/year where the number of  the suitable fishing trips was 470 trips.